Psychological factors and perceptions of pain associated with dental treatment - Maggirias J, Locker D. (Blackwell Synergy, 2002)
Although pain during dental treatment has been identified as playing a major role in the onset of dental anxiety and is a major concern of patients when seeking dental care, there have been very few studies of the prevalence of pain during dental treatment and the factors associated with patients’ perceptions of pain.